The interaction of person and number in Mi’gmaq - Coon, Jessica; Bale, Alan (Nordlyd, 2014)
This paper presents puzzles concerning the representation of features in the agreement system of the Eastern Algonquian language, Mi’gmaq. A growing body of research converges on the idea that φ-agreement should be separated into distinct person (π0), number (#0), and sometimes gender (γ0) probes (e.g. Anagnostopoulou 2003, Béjar 2003, Béjar and Rezac 2003, Laka 1993, Shlonsky 1989, Sigurðsson 1996, Sigurðsson and Holmberg 2008, Preminger 2012). While these proposals account well for agreement and partial agreement patterns in a number of languages, we show that in order to account for the agreement system of Mi’gmaq, π0 and #0 must probe together, which we argue to be the result of fusion of two distinct probes. We discuss the implications of Mi’gmaq agreement for “prominence hierarchies” and feature geometries in the grammar.